Plasmon resonance measurements in pool boiling, condensation and evaporation experiments on a nanostructured surface. (March 2022) - Lefèvre, F.; Al Masri, M.; Ibrahim, J.; Veillas, C.; Verrier, I.; Celle, F.; Parriaux, O.; Jourlin, Y.; Cioulachtjian, S.
Abstract: Surface plasmon resonance (SPR) is used in a wide range of applications, including biology, physics and materials science, because of its ability to obtain sub-wavelength measurements from a simple white light source, in real time and non-invasively. Surprisingly, this technique is just beginning to be used in the field of phase change heat transfer, whereas fundamental phenomena occurring near interfaces, such as ice, liquid or vapour nucleation, require the development of innovative techniques capable of reaching this little-explored scale. In this paper, the grating-coupled SPR method is implemented on aluminium samples on which different liquid-vapour phase change phenomena take place. The first goal of this work was the study of the influence of the surface topography on the boiling phenomenon, in particular in the presence of geometrical patterns of micrometric and sub-micrometric scales, typical of those necessary for the implementation of the grating-coupled SPR method. The results show that mirror-polished surfaces covered with periodically structured sub-micrometric grooves have the best thermal characteristics amongst the different surfaces tested, similar to those of a mirror-polished surface with a small number of holes evenly distributed over the surface. Sub-micrometre scale corrugated surfaces being also ideally suited for SPR, they were also used in the second part of the paper to evaluate the potential of this method for the study of boiling, condensation and evaporation. Although our optical SPR test bench, limited by its acquisition frequency, was not able to detect the very fast birth of the first vapour nuclei at the beginning of nucleate boiling, the results yet show the interest of the method as a non-intrusive technique to measure the temperature of the liquid in the very vicinity of the wall, which is also an essential measurement. In addition, measurements from the condensation and evaporation experiments show that SPR provides a useful means to monitor the formation of a nanoscale condensation film and the evaporation of an acetone film in real time. This exploratory study opens perspectives to understand the small-scale phenomena that occur during phase changes and thus help develop functional surfaces that promote or delay their occurrence.